Laboratory manual and workbook in general inorganic chemistry - De Castro, Herminia G.; Semira, Estrelita Rivera; Tolentino, Angelina G.; Bhagwani, Ernie T. (Quezon City Great Books Trading, 2003)
A manual which aims to provide information to Inogranic Chemistry students through the different activities and experiments included. Intented for the use of teachers and students of Inorganic Chemistry and of students who are studying other allied sciences.
Keywords: Chemistry, Inorganic -- Laboratory manuals